Quantum Trading : Using Principles of Modern Physics to Forecast the Financial Markets - Oreste, Fabio (Hoboken : John Wiley & Sons, 2011)
A cutting-edge guide to quantum trading Original and thought-provoking, Quantum Trading presents a compelling new way to look at technical analysis and will help you use the proven principles of modern physics to forecast financial markets. In it, author Fabio Oreste shows how both the theory of relativity and quantum physics is required to makes sense of price behavior and forecast intermediate and long-term tops and bottoms. He relates his work to that of legendary trader W.D. Gann and reveals how Gann's somewhat esoteric theories are consistent with his applications of Einstein's theory of.
CHAPTER 10 Forecasting Tops and Bottoms Using QPLs and SubharmonicsCHAPTER 11 Time Algorithms in Quantum Trading; CHAPTER 12 How to Use All the Trading Tools Together; CHAPTER 13 How to Use Options: Unlimited Gains with Little Risk; CHAPTER 14 Options Strategies with Quantum Trading Tools; CHAPTER 15 A Toast to a New Achievement in Trading; Conclusion: Making Peace with Mr. Market; Acknowledgments; About the Author; Index.
Print version record.
Keywords: Speculation; Stocks; Quantum theory; Physics; Physics; Quantum theory; Speculation; Stocks; BUSINESS & ECONOMICS -- Investments & Securities -- General; Physics; Quantum theory; Speculation; Stocks; Electronic books